KNACK online: An evidence-based website developed to address adolescent obesity - Kidd, Tandalayo; Johannes, Elaine; Simonson, Larry; Medeiros, Denis (My University, 2008)
Nearly 9 million children and adolescents are overweight in the United States. The prevalence of overweight children aged 6-11 and overweight adolescents aged 12-19 has more than tripled in the past 30 years.1 Recognizing overweight and obese children may be quite easy. However, contributing factors such as family, medical, and/or dietary history and associated risk factors such as hypertension, heart disease, and diabetes make addressing the verweight/obese issue complex.2 The Institute of Medicine3 recommends multiple stakeholders from various segments of society, including families and communities, to address this growing public health problem. The purpose of this project was to develop an evidence-based website that provided parents, community advocates, and youth workers reliable, useful and action-oriented resources to address early adolescent (ages 11-14) obesity.
Keywords: Adolescent obesity; Nutrition; Physical activity; Community health; Web site development